Incidence and Outcome of Invasive Fungal Diseases in Children With Hematological Malignancies and/or Allogeneic Hematopoietic Stem Cell Transplantation: Results of a Prospective Multicenter Study - Lehrnbecher, Thomas; Schöning, Stefan; Poyer, Fiona; Georg, Jamina; Becker, Andreas; Gordon, Kathrin; Attarbaschi, Andishe; Groll, Andreas H. (Frontiers in Microbiology, 2019)
Background: Available data on the incidence and outcome of invasive fungal diseases (IFD) in children with hematological malignancies or after allogeneic hematopoietic stem cell transplantation (HSCT) are mostly based on monocenter, retrospective studies or on studies performed prior to the availability of newer triazoles or echinocandins. Procedure: We prospectively collected clinical data on incidence, diagnostic procedures, management and outcome of IFD in children treated for hematological malignancies or undergoing HSCT in three major European pediatric cancer centres. Results: A total of 304 children (median age 6.0 years) who underwent 360 therapies (211 chemotherapy treatments, 138 allogeneic HSCTs and/or 11 investigational chemotherapeutic treatments) were included in the analysis. Nineteen children developed proven/probable IFD, mostly due to Aspergillus (n=10) and Candida spp (n=5), respectively. In patients receiving chemotherapy, 11 IFDs occurred, all during induction or re-induction therapy. None of these patients died due to IFD, whereas IFD was lethal in 3 of the 8 HSCT recipients with IFD. Significant differences among centers were observed with regard to the use of imaging diagnostics and the choice, initiation and duration of antifungal prophylaxis. Conclusions: This prospective multicenter study provides information on the current incidence and outcome of IFD in the real life setting. Practice variation between the centers may help to ultimately improve antifungal management in children at highest risk for IFDs.